Contemporary Grading of Prostate Cancer: The Impact of Grading Criteria and the Significance of the Amount of Intraductal Carcinoma - Vasiliki Tzelepi (MDPI AG, 2021)
(1) Background: Prognostic grade group (PGG) is an important prognostic parameter in prostate cancer that guides therapeutic decisions. The cribriform pattern and intraductal carcinoma (IDC) are two histological patterns, that have additional prognostic significance. However, discrepancies exist regarding the handling of IDC according to the guidelines published by two international genitourinary pathology societies. Furthermore, whether, in addition to its presence, the amount of IDC is also of importance has not been studied before. Lastly, the handling of tertiary patterns has also been a matter of debate in the literature. (2) Methods: A total of 129 prostatectomy cases were retrieved and a detailed histopathologic analysis was performed. (3) Results: Two cases (1.6%) upgraded their PGG, when IDC was incorporated in the grading system. The presence and the amount of IDC, as well as the presence of cribriform carcinoma were associated with adverse pathologic characteristics. Interestingly, in six cases (4.7%) there was a difference in PGG when using the different guidelines regarding the handling of tertiary patterns. In total, 6.2% of the cases would be assigned a different grade depending on the guidelines followed. (4) Conclusions: These findings highlight a potential area of confusion among pathologists and clinicians and underscore the need for a consensus grading system.